2012
DOI: 10.1038/eye.2012.156
|View full text |Cite
|
Sign up to set email alerts
|

A study of slippage of various knot configurations

Abstract: Eye

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…4 In another study, the slip knot and modified slip knot demonstrated greater than 2 times more slippage after 24 hours than the surgeon's knot. 7 Herein, we present an alternative technique for tying a 3-1-1 square knot, reducing its crosssectional area while burying the knot, thus reducing the likelihood of suture breakage.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 In another study, the slip knot and modified slip knot demonstrated greater than 2 times more slippage after 24 hours than the surgeon's knot. 7 Herein, we present an alternative technique for tying a 3-1-1 square knot, reducing its crosssectional area while burying the knot, thus reducing the likelihood of suture breakage.…”
mentioning
confidence: 99%
“…Each of these techniques produces a smaller knot that requires less force when burying. 4,7,8 The slip knot and modified slip knot in particular offer the additional benefit of tension adjustment until after the third throw. The trade-off, however, is that these alternatives produce sutures with reduced tensile strength compared with the traditional 3-1-1 technique.…”
mentioning
confidence: 99%
See 1 more Smart Citation